Nitrogen-Modified Titanium Dioxide as an Adsorbent for Gaseous SO - Agnieszka Wanag; Ewelina Kusiak-Nejman; Joanna Kapica; Łukasz Kowalczyk; Antoni W. Morawski (Adsorption Science & Technology)
In this study, sorption of gaseous SO 2 on nitrogen-modified titanium dioxide (TiO 2 /N) materials was investigated. The TiO 2 /N materials were prepared by thermal modification of commercial TiO 2 in gaseous ammonia flow. First, TiO 2 was calcined at 100–700 °C (Δt = 200 °C). The obtained samples were then rinsed with water to remove the residual ammonium groups adsorbed on the TiO 2 surface. The influence of modification temperature, BET surface area, pore volume and nitrogen content on the efficiency of SO 2 sorption on TiO 2 surface was discussed. The best result was obtained for nitrogen-modified material that is heat treated at 100 °C. The total sorption capacity calculated for this sample was 20.96 mg SO 2 /1 g TiO 2 . It was shown that TiO 2 modified with nitrogen at low temperature can be a very effective sorbent in capturing SO 2 particles.